Dorothy must die - Paige, Danielle (Novelist) (Paige, Danielle (Novelist). Dorothy must die series, 2014)
Amy Gumm, the other girl from Kansas, has been recruited by the Revolutionary Order of the Wicked to stop Dorothy who has found a way to come back to Oz, seizing a power that has gone to her head -- so now no one is safe!